Combination of chiral linkers with thiophenecarboximidamide heads to improve the selectivity of inhibitors of neuronal nitric oxide synthase - Jing, Qing; Li, Huiying; Roman, Linda J; Martásek, Pavel; Poulos, Thomas L; Silverman, Richard B (Bioorganic & medicinal chemistry letters, 2014)
To develop potent and selective nNOS inhibitors, a new series of double-headed molecules with chiral linkers that derive from natural amino acid derivatives have been designed and synthesized. The new structures integrate a thiophenecarboximidamide head with two types of chiral linkers, presenting easy synthesis and good inhibitory properties. Inhibitor (S)-9b exhibits a potency of 14.7 nM against nNOS and is 1134 and 322-fold more selective for nNOS over eNOS and iNOS, respectively. Crystal structures show that the additional binding between the aminomethyl moiety of 9b and propionate A on the heme and tetrahydrobiopterin (H4B) in nNOS, but not eNOS, contributes to its high selectivity. This work demonstrates the advantage of integrating known structures into structure optimization, and it should be possible to more readily develop compounds that incorporate bioavailability with these advanced features. Moreover, this integrative strategy is a general approach in new drug discovery.
Keywords: Models, Molecular; Selective inhibition; imidy; Protein crystallography; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Thiophenes; Tetrahydrobiopterin; Dose-Response Relationship, Drug; synthasa oxidu dusnatého, typ I; molekulární modely; molekulární struktura; Molecular Structure; Thiophenecarboximidamide; Imides; inhibitory enzymů; Nitric Oxide Synthase Type I; vztah mezi dávkou a účinkem léčiva; thiofeny; Heme; Nitric oxide synthase; Enzyme Inhibitors